Use of reclaimed asphalt pavement – necessity and innovation - Bańkowski, Wojciech; Sybilski, Dariusz; Król, Jan; Kowalski, Karol; Radziszewski, Piotr; Skorek, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
A responsible recycling of asphalt pavements is crucial in terms of economic and ecological measures related to preservation of non-renewable resources of bituminous binders and aggregates. Leading countries in road industry endeavour to maximise reclaimed asphalt pavement (RAP) application in production of new asphalt mixtures. Unfortunately, RAP re-using in Poland is limited and often results in construction works related to verge tabilization or construction of a subbase in mineral-cement-emulsion (MCE) technology. Application of RAP in asphalt mixture production, if happened, would be restricted to cold RAP addition in a limited amount only. The aforementioned situation is mostly related to lack of contractor’s experience, HMA plants not equipped with the necessary installation, agencies restrictions, tender conditions, problems with RAP homogeneity and others. This paper presents InnGA research project in which the main goal was to develop the asphalt mixtures with as high as possible RAP content without compromising mixture performance. Project and its dissemination should provide necessary know-how to road authorities, agencies, design offices and contractors.